The role of chitosan and natural polymer in growth parameters of Senna occidentalis L. under water stress conditions - Shaimaa Al-Hutaimy (Journal of Kerbala for Agricultural Sciences, 2026)
A factorial experiment was conducted in a plastic greenhouse designated for this purpose in Al-Husseiniya sub-district (14 km southeast of Karbala province) to study the effect of natural compounds on the growth of plants under water stress. The experiment included three equally important factors: the first factor involved three irrigation intervals (4, 6, and 8 days), the second factor involved treating the soil medium with different levels of fabric polyter (0.0, 2.5, and 5.0 g per pot), and the third factor involved foliar spraying with different concentrations of nano-chitosan (0.0, 100, and 200 mg L⁻¹).The experiment was designed in a randomized complete block design (RCBD) with three replicates for each treatment, with each replicate consisting of three experimental units. Each pot represented an independent experimental unit, with one plant per pot.The results showed significant differences in growth parameters due to the studied factors. The combination treatment of 2.5 g polyter and foliar spraying with 200 mg L⁻¹ chitosan for plants irrigated every 4 days resulted in significantly superior performance in plant height (127.67 cm), number of leaves (444.3 leaves), and number of roots (8.33 roots), which did not differ significantly from the same combination when irrigated every 8 days. Leaf chlorophyll content also increased (60.43 SPAD units). The longest root length (38.67 cm) was observed in the combination of 5.0 g polyter and water-only spraying under 8-day irrigation intervals. The lowest values were recorded in the control treatment. These findings suggest that eco-friendly and sustainable environmental factors have a significant impact on enhancing the vegetative growth parameters of Senna occidentalis L.under varying irrigation intervals.